Defective metal–organic framework derivative by room-temperature exfoliation and reduction for highly efficient oxygen evolution reaction. Issue 23 (28th May 2019) - Zou, Zehua; Cai, Minmin; Zhao, Xiaohua; Huang, Junfeng; Du, Jing; Xu, Cailing
Abstract : Metal–organic frameworks (MOFs) have been considered attractive precursors to fabricate functional MOF derivatives for oxygen evolution reactions (OER). Abstract : Metal–organic frameworks (MOFs) have been considered attractive precursors to fabricate functional MOF derivatives for oxygen evolution reactions (OER). Herein, we developed a simple room-temperature exfoliation and reduction strategy to construct a core–shell structure electrocatalyst derived from multi-layer MOF precursor for an enhanced OER performance. The reduced MOFs displayed stable OER current with an overpotential as low as 253 mV at 10 mA cm −2, a Tafel slope of 39 mV dec −1 and a TOF increased by 38 times compared to pristine MOFs. The significant boosting is attributed to the amorphous core–shell structure providing more active sites and sufficient inner defects to enhance the conductivity by NaBH4 reduction under ambient conditions.